Ms Glow Online Reputation Management Regarding Public Manipulation by Appearing at Paris Fashion Week - Untari Salsabila, Kania; Wa’dah, Habibatul; Meilina, Indah (PT Literasi Nusantara Publisher, 2023)
Building and maintaining a reputation for a company takes a long time, but a reputation can be destroyed instantly. Companies must have good reputation management so that when they get an issue, they can immediately deal with it. This research uses descriptive qualitative methods by reading news journals about the issues raised. The results of this study indicate that as a company with a good reputation, Ms. Glow tries to deal with every problem in her company in a good way. Providing timely statements clarifying what is going on keeps matters from becoming too lengthy. An apology was also conveyed by the owner on his personal Instagram story page for responding emotionally to this problem; he admitted that he had misrepresented yesterday's situation and did not deserve to be like that.